Rocket and radar investigation of background electrodynamics and bottom-type scattering layers at the onset of equatorial spread F - Hysell, D. L. (2006)
Sounding rocket experiments were conducted during the NASA EQUIS II campaign on Kwajalein Atoll designed to elucidate the electrodynamics and layer structure of the postsunset equatorial F region ionosphere prior to the onset of equatorial spread F (ESF). Experiments took place on 7 and 15 August 2004, each comprised of the launch of an instrumented and two chemical release sounding rockets. The instrumented rockets measured plasma number density, vector electric fields, and other parameters to an apogee of about 450 km. The chemical release rockets deployed trails of trimethyl aluminum (TMA) which yielded wind profile measurements. The Altair radar was used to monitor coherent and incoherent scatter in UHF and VHF bands. Electron density profiles were also measured with rocket beacons and an ionosonde. Strong plasma shear flow was evident in both experiments. Bottom-type scattering layers were observed mainly in the valley region, below the shear nodes, in westward-drifting plasma strata. The layers were likely produced by wind-driven interchange instabilities as proposed by Kudeki and Bhattacharyya (1999). In both experiments, the layers were patchy and distributed periodically in space. Their horizontal structure was similar to that of the large-scale plasma depletions that formed later at higher altitude during ESF conditions. We argue that the bottom-type layers were modulated by the same large-scale waves that seeded the ESF. A scenario where the large-scale waves were themselves produced by collisional shear instabilities is described.